Opportunities and instruments of strategic planning for the development of Russian football - A. V. Orlov; A. V. Babakov (Путеводитель предпринимателя)
The article discusses the opportunities and mechanisms for strategic planning and proposals for the establishment of the Federal Fund to Support Russian football (FFSF) for acceleration of the development of football infrastructure: construction of stadiums, providing youth sports schools, support the preparation of new and upgrading of existing coaching staff considering approaching World Football Cup-2018. The legislative initiative on limiting Russian footballers’ wages level is also analyzed in the article.